Reliability Assessment of Masonry Infilled RC Frame Building’s Earthquake Performance through Accidental Torsion Consideration - Dalibor Burilo; Damir Markulak; Tihomir Dokšanović; Davorin Penava (Civil Engineering Journal, 2023)
Accidental torsional behaviour induced by horizontal loading is difficult to predict, being a complex phenomenon governed by many variables. This problem gains an additional dimension of complexity when nonlinear responses with imperfections need to be considered. Therefore, evaluation and understanding the influence of accidental torsion are fundamental in seismic reliability estimation. This study offers vital insights based on the results of a 1/2.5 scale three-story masonry infilled reinforced concrete frame building’s test on a shaking table. The building was tested under ten consecutive ground motions with increasing ag/g, recorded at Herzeg Novi station during the 1979-M6.9 Montenegro earthquake. The accidental eccentricity, considered a random variable, resulted from unsymmetrical masonry infill wall damage in an otherwise regular building. Its effect, in relation to that of other random (design) variables, was evaluated utilising weight factors and, in addition, assessed through various building code provisions and state-of-the-art research findings. The analysis revealed that the accidental eccentricity, as compared to other random variables considered, could, under certain conditions, reach values higher than those prescribed by the building codes. This unacceptable seismic reliability clearly warns that accidental torsion of masonry-infilled reinforced concrete frames in in-situ conditions must be considered even in regular buildings. Doi: 10.28991/CEJ-2023-09-02-017 Full Text: PDF